2019
DOI: 10.1002/slct.201902049
|View full text |Cite
|
Sign up to set email alerts
|

Paired Spectroscopic and Crystallographic Studies of Proteases

Abstract: The active sites of subtilisin and trypsin have been studied by paired IR spectroscopic and X‐ray crystallographic studies. The active site serines of the proteases were reacted with 4‐cyanobenzenesulfonyl fluoride (CBSF), an inhibitor that contains a nitrile vibrational reporter. The nitrile stretch vibration of the water‐soluble inhibitor model, potassium 4‐cyanobenzenesulfonate (KCBSO), and the inhibitor were calibrated by IR solvent studies in H2O/DMSO and the frequency‐temperature line‐slope (FTLS) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Its control, subtilisin, was inhibited by PMSF but not by EDTA, indicating subtilisin as being a serine protease. Other studies showed the presence of calcium ions in the subtilisin structure, as determined by X-ray crystallography (Luo et al 2019). Calcium ions are also described as structural stabilizers in some enzymes, such as subtilisin and thermolysin.…”
Section: Discussionmentioning
confidence: 92%
“…Its control, subtilisin, was inhibited by PMSF but not by EDTA, indicating subtilisin as being a serine protease. Other studies showed the presence of calcium ions in the subtilisin structure, as determined by X-ray crystallography (Luo et al 2019). Calcium ions are also described as structural stabilizers in some enzymes, such as subtilisin and thermolysin.…”
Section: Discussionmentioning
confidence: 92%